Utilizing al amr bil ma’ruf and wa nahyu ‘anil munkar for corporate governance and human capital development - Sarif, Suhaimi Mhd; Ismail, Yusof (2012)
This research paper examines the effects of Islamic integrity concept on corporate governance and human capital development. The research uses Islamic ethical philosophy into the corporate integrity framework for enhancing corporate governance for reputation purpose. This research also contributes to a perspective on the knowledge of promotion of goodness (al amr bil ma’ruf) and prevention of evil (wa nahyu ‘anil munkar) into corporate governance and human capital development of public companies. In the modern managerial paradigm, managers are expected to get things done in organizations through their fellow colleagues efficiently and effectively. The study uses Al Qurtubi and Ibn Taymiyyah models in operationalizing the promotion of goodness (al ‘amr bil ma’aruf) and prevention of evil (wa nahyu anil munkar) in modern public companies’ corporate environment. The study uses content analysis on secondary data and information of Bursa Malaysia public companies’ annual reports, Internet search engine hit analyses, selected literature on corporate governance and website information of 100 public companies. The results of the content analysis suggested 13 factors that contributed to good corporate governance. Business decision makers are recommended to use the 13-factor checklist for corporate governance practices assessment. The study also proposed 15 actions to use good corporate governance practices to achieve sustainable organizational performance. The study conducted survey and personal interviews but the results were not statistically significant and meaningful. The study proposes the future study to use survey and personal interview.